Effect of the binary compound method of TOR promoting dissolution and NaOH solution surface treatment on the performance of rubber asphalt. (25th October 2021) - Liu, Li; Liu, Zhaohui; Yang, Chengcheng; Huang, You; Li, Wenbo
Highlights: Rubber asphalt are prepared by treating CRP with NaOH solution and adding TOR. The optimum concentration of NaOH solution and content of TOR are determined. Micro mechanism of NaOH and TOR on rubber asphalt are investigated. Properties of binary compound modified rubber asphalt are evaluated. Abstract: In view of the problems of poor high-temperature storage stability, high viscosity and easy segregation of rubber powder modified asphalt, the rubber asphalt was prepared using a binary combination of surface treatment crumb rubber powder (CRP) in NaOH solution and a doped trans-polyoctenamer rubber reactant (TOR). Through asphalt softening point, penetration, ductility and segregation tests, a reasonable concentration of 2% NaOH for surface treatment of CRP and an optimum content of 4.5% for TOR were determined. The microscopic mechanism of NaOH and TOR on rubber asphalt was analyzed by tests such as scanning electron microscopy and infrared spectroscopy, and the performance of binary compound modified asphalt (NT-RA) was analyzed using segregation test, bending beam rheometer (BBR), dynamic shear rheology (DSR) and Brinell rotational viscosity test. The results show that NaOH solution could remove impurities on the surface of CRP and improve the interfacial adhesion state between asphalt, and TOR can promote the dissolution of CRP in asphalt. The binary compound action significantly improves the storage stability, low-temperature performance and high-temperature performance of rubber asphalt, and effectively reduces the viscosity of rubber asphalt.